Effects of 24 Weeks Combined Rehabilitation Exercise Program on Functional Recovery in Obsess High Tibial Osteotomy Patients - Min-Ah Kim; Kwang-Jin Lee; Keun-Ok An (Asian Society of Kinesiology, 2022)
OBJECTIVES This study aims to investigate the effects of a 24 weeks combined rehabilitation exercise program on the subjective questionnaire, isokinetic muscle function test and dynamic balance test of high tibial osteotomy patients with normal weights and obese individuals. METHODS Sixteen tibial osteotomy patients were recruited in the study. They were divided into two groups(normal weight group[n=8] or obesity weight group[n=8]). A pre-test consisting of subjective questionnaire, isokinetic muscle function test and Y balance test. Using the same test in 12 weeks, 24 weeks after the surgery. All groups completed the rehabilitation exercise program for the duration of 24 weeks. RESULTS The significant interaction was observed between group and time on the involve bilateral flexor strength deficits (p=.045) and the posteromedial reach distance (p=.041). CONCLUSIONS These results suggest that a 24 weeks rehabilitation exercise program is needed after high tibial osteotomy in order to restore the same level of activity as before surgery.